TA’LIM JARAYONINI TAKOMILLASHTIRISHDA PEDAGOGIK QOBILIYATLARNING O‘RNI (Ustozlar uchun, 2024)
This article is about the importance of pedagogical skills in improving the educational process of a pedagogue, organizing lessons. The article also reflects the demands of today's teachers.